DECENTRALIZATION OF HOUSING POLICY FOR LOW-INCOME COMMUNITIES IN URBAN AREAS: AN ANALYSIS OF POLITICAL, FISCAL AND, ADMINISTRATIVE POLICY - Ahmad Sururi (Jurnal Pengembangan Kota, 2022)
The purpose of this study is to discuss housing decentralization policies for urban Low-Income Communities based on three decentralization issues, namely politics, fiscal, and administration, and to recommend the concept of housing decentralization as an instrument and housing policy reform.  The idea of decentralization of housing policy can’t be separated from various problems such as the debate over the authority of housing policy, the dependence of the regional government's housing budget on the central government, and various other obstacles. This study employed academic literature review related to decentralization studies and housing policies. The results of the study show that the three decentralization issues that are correlated with urban housing policies for Low-Income Communities have not yet fully provided an optimal impact on the realization of the ideal and desirable urban housing policies for Low-Income Communities. However, the very strong relationship between the three issues of decentralization and urban housing policy can be an important idea and recommendation to promote housing decentralization as an instrument and direction of urban housing policy reform for Low-Income Communities in Indonesia in the future.